2000
DOI: 10.1029/1999jd901163
|View full text |Cite
|
Sign up to set email alerts
|

Local mean state changes due to gravity wave breaking modulated by the diurnal tide

Abstract: Abstract. During gravity wave breaking, heating rates are determined by wave advection, turbulent diffusion, and turbulence dissipative heating. A series of numerical experiments show that the total heating rates can be larg (--• +10 Kh -1) and can cause large local temperature changes. The wave advection causes dynamical cooling in most of the wave breaking region, consistent with previous studies. Nonuniform vertical turbulent diffusion causes strong transient heating in the lower part of the wave breaking r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
110
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 27 publications
7
110
1
Order By: Relevance
“…Lidar observations at mid-latitudes by Whiteway et al (1995); Thomas et al (1996); Liu et al (2004) and high-latitudes by Cutler et al (2001); Duck and Greene (2004); Collins et al (2011) have shown that MILs are often associated with turbulence activity which is reflected in the lidar temperature measurements as an adiabatic lapse rate on top of the inversion layers. On the other hand, numerical simulations by Liu et al (2000) showed that vigorous turbulence is required to change the thermal structure to the shape associated with temperature inversions. Also, Thomas et al (1996) found a connection between MILs observed with Rayleigh lidar and winter radar echoes observed by their VHF radar, and concluded that the reason was strong turbulence activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lidar observations at mid-latitudes by Whiteway et al (1995); Thomas et al (1996); Liu et al (2004) and high-latitudes by Cutler et al (2001); Duck and Greene (2004); Collins et al (2011) have shown that MILs are often associated with turbulence activity which is reflected in the lidar temperature measurements as an adiabatic lapse rate on top of the inversion layers. On the other hand, numerical simulations by Liu et al (2000) showed that vigorous turbulence is required to change the thermal structure to the shape associated with temperature inversions. Also, Thomas et al (1996) found a connection between MILs observed with Rayleigh lidar and winter radar echoes observed by their VHF radar, and concluded that the reason was strong turbulence activity.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observations show that temperature inversions are often associated with a near adiabatic lapse rates above the inversion layer (Whiteway et al, 1995;Duck et al, 2001), which is clearly indicative of turbulence activity in those regions. However, numerical simulations showed that only vigorous turbulence revealing heating rates of ∼ 10 K h −1 is capable of producing temperature inversions (Liu et al, 2000). Such strong turbulence, however, has rarely been observed (see, e.g., Lübken, 1997;Lübken et al, 2002) in contrast to the temperature inversion layers, which are common phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…This is important for several reasons, among which are the fact that a large-scale TIL may comprise a stable duct for longdistance propagation of gravity waves, and/or support mesospheric undular bores . This may also shed some light on the role of gravity waves in producing TILs [Huang et al, 1998;Liu et al, 2000]. We therefore sought layers that were similar in amplitude and altitude within sequences of consecutive events.…”
Section: Mesospheric Temperature Inversion Layersmentioning
confidence: 99%